Educação e desenvolvimento humano: um estudo avaliativo da qualidade e da política educacional do ensino médio de 2007 a 2017 no estado do Ceará - Oliveira, José Valmir Guimarães de (2022)
The thesis has as title: Education and Human Development: An Evaluative Study of the Quality and Educational Policy of High School from 2007 to 2017, in the State of Ceará, because in 2017, in addition to continuing to advance in elementary education indicators, Ceará registered at IDEB, a significant advance in the High School level, jumping from a grade of 3.40 to 3.84, which allows it to be among the four states in this stage of education, where it previously occupied the 14th position. Thus, our problem in describing the scenario of measuring results by numerical indicators, control and monitoring, which has as its main effect the overestimation of a pedagogy of competition and accountability for the achievement of goals, giving second place to social contexts, a transformative learning and the subjectivity of students. Based on this surprising advance, seek to present an evaluative study on the quality and educational policy of High School from 2007 to 2017 and the following actions, in the State of Ceará, with the following specific objectives: 1) Contextualize the trajectory of the Educational Policy of Secondary Education, from the educational reforms of the 1990s to the current mechanisms of accountability, educational performance and cooperation (public-private) that resulted in the current educational policies developed by the State of Ceará; 2) Describe the main actions and/or strategies of the educational policy that raised the educational quality indexes in Ceará High School, identifying its main actors and their most expressive contributions; 3) To present the position of specialists in educational evaluation regarding the Ceará educational evaluation model and the operationalization of its results and 4) To present evaluative studies on the quality of Ceará's secondary education in the light of Hegel's developmental epistemology. The assumptions are aimed at understanding Education as essential for human development, with consequences both in the economic and social horizons, emphasizing the intention to expand the human competence of the subjects, but it is seen that the results of large-scale assessments that the Ceará educational system is submitted (Ex.: SPAECE/SAEB) they only explain the aspects of the quantitative paradigm, distancing themselves from a model supported in the formation for citizenship, for social practices and for the world of work. They point to the analysis of the Educational Management by Results – GEpR model, the result of the SEDUC-Instituto Unibanco partnership, called Management Circuit (accountability, monitoring and evaluation of school indicators present in the composition of IDEB), responsible for improving the results of secondary education Ceará. The methodological structure used is the Quadripolar, created by De Bruyne, Herman and Schoutheete (1991), structured in four distinct and integrated poles. The poles are constituted as follows: The epistemological pole brings the Dialectic approach of F.W.G. Hegel (1781-1831), carried out in three phases (thesis, antithesis and synthesis - relevance, contradictions and overcomings), through which it is intended to understand Ceará's assessment along the categories: Development, Educational Quality, Educational Assessment and Educational Policy. In the theoretical pole, the frame of reference is idealist-rationalist, guided mainly by Lima (2008), Pedro Demo (1991), Charlot (2008), Shiromo (2010), Vieira (2010) and DemervalSaviani (1999). In the morphological pole (structuring/causality), the exhibition of the main educational models proposed by SEDUC (PAIC; GEpR; AprenderpraValer and integral and professional schools). The technical center controls data collection, brings the trajectory of educational policy strategies, the evolution of learning levels and the position of stakeholders (stakeholders), with managers and former educational managers and specialists in educational evaluation on the evaluation model of Ceará and its educational quality. The methodological procedures applied are the Historical and Comparative methods, analyzing the quality, human development, the evaluation system and the educational policy for secondary education, from 2007 to 2017, in a reinterpretation of Educational Accountability. The collection of the content of the interviews will be through the Atlas TI software (qualitative analysis software) and relating the interviews with the reading of educational indicators (SPAECE/SAEB) for the year 2017.